The use of roadmaps in innovation-oriented planning (Research, Society and Development, 2020)
The objective of this work is to present a conceptual model for the use of roadmaps in planning oriented to innovation, considering the functional perspectives of the organization, the behaviors of its employees and leaders, the existing and potential partnerships, as well as the conditions and turbulences of the market in which acts or intends to act. Based on the consultation of scientific literature in the area and taking as a reference models of roadmaps already used in innovative industries, it is discussed how these can be used to develop the innovation-oriented planning of organizations. As a result of the research carried out, a conceptual model is proposed for the use of the roadmap in innovation planning, which can be adjusted or customized for each organization, be it manufacturing or services or even public or private organizations. In the developed model, six dimensions of analysis are proposed: the market involving competitors, partnerships, customers, threats, opportunities and strategy; current technologies and trends; Products and Services, Processes and Resources involving finance, facilities, infrastructure and R&D projects.